The relationship between linguistic features and readability of Dini Integrated Curriculum Arabic textbook in Government-Aided Religious School - Mohd Fadzli Ismail,; Nik Mohd Rahimi Nik Yusoff, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Efforts to strengthen the Arabic language subject can further strengthen the flow of the Dini Integrated Curriculum (KBD) in Malaysia. The mastery of this subject can be measured based on the readability of students’ text. This study aims to identify the readability of the KBD Form Four Arabic textbook (al-Lughah al-Arabiah al-Muasirah) in Government Aided Religious Schools (SABKs) based on linguistic characteristics. A quantitative survey design was implemented on 694 students in five SABK zones using the proportional strata random sampling technique. The technique has passed the instrument validity and reliability tests. Data were analyzed by text, descriptive, and inferential analyses including frequency, percentage, mean, standard deviation, Kuder Richardson 20 test, and Pearson’s correlation test. The findings of the study of linguistic features show that word form dominates a high level of uniformity in the text for word category and Balagha for sentence category, while the content category is in the moderate level. The readability of the textbook is at a disappointing level. There is a strong significant relationship between verb sentences and long verb sentences with the readability of the KBD Form Four Arabic textbook. The results of the study can also be utilized by authorities to ensure the materials in Arabic textbooks can attract students to continue reading and learning more actively.